Adolescent alcohol and cannabis use and early adulthood educational attainment in the 1986 Northern Finland birth cohort study - Levola, Jonna; Alakokkare, Anni Emilia; Denissoff, Alexander; Mustonen, Antti; Miettunen, Jouko; Niemelä, Solja (BMC Public Health, 2024)
Background: Heavy alcohol and cannabis use during adolescence have been previously described as risk factors not only for morbidity in adulthood, but also social problems including adversities in educational attainment. Attempts to consider overlapping risk factors and confounders for these associations are needed. Methods: Using weighted multivariable models, we examined prospective associations between age at first drink (AFD), age at first intoxication (AFI), frequency of alcohol intoxication, as well as self-reported alcohol tolerance (i.e., number of drinks needed for the subjective experience of intoxication), and lifetime cannabis use at age 15/16 years with subsequent educational attainment obtained from comprehensive registers until age 33 in the Northern Finland Birth Cohort 1986 (6,564 individuals, 49.1% male). Confounding variables including sex, family structure (intact vs. non-intact), maternal and paternal education level, behavioural/emotional problems in school at age 7/8 years, having a history of illicit substance use in adolescence, having any psychiatric diagnosis before age 16, and parental psychiatric diagnoses, were adjusted for. Results: In this large birth cohort study with a 17-year follow-up, younger age at first intoxication, higher frequency of alcohol intoxication, and high self-reported alcohol tolerance at age 15/16 years were associated with poorer educational outcomes by the age of 33 years. These associations were evident regardless of potential confounders, including parental education and childhood behavioural/emotional problems. The association between adolescent cannabis use and educational attainment in adulthood was no longer statistically significant after adjusting for confounders including frequency of alcohol intoxication at age 15/16. Conclusions: Assessments of age of first alcohol intoxication, high self-reported alcohol tolerance and frequency of intoxication during adolescence should be included when implementing screening strategies aimed at identifying ...